Fixed Point Theorems of Fuzzy T*-Cone Metric Space and Their Integral Type Application - Hadi, Sarim H. (Iraqi Journal of Science, 2019)
The objective of this work is to study the concept of a fuzzy -cone metric space And some related definitions in space. Also, we discuss some new results of fixed point theorems. Finally, we apply the theory of fixed point achieved in the research on an integral type.